Dixon, descending : a novel - Outen, Karen ([New York] : Dutton, 2024)
"Dixon was once an Olympic-level runner. When his charming older brother, Nate, suggests that they attempt to be the first Black American men to summit Mount Everest, Dixon can't refuse. Once on the mountain, they are met with extreme weather conditions, oxygen deprivation, and precarious terrain. But as much as they've prepared for this, Mt. Everest is always fickle. And in one devastating moment, Dixon's world is upended."--
Keywords: Middle class African Americans -- Fiction; African American men -- Fiction; Brothers -- Fiction; Mountaineering -- Everest, Mount (China and Nepal) -- Fiction; Everest, Mount (China and Nepal) -- Fiction; Sports fiction; Action and adventure fiction